The Analysis of World Trade Organization Panel Decision of Indonesia Measures Relating to Raw Materials - Daffa Brilliandana Pratama (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
European Union has requested a panel regarding Indonesia's restriction of exports and downstreaming of raw materials. According to the European Union, Indonesia's export and downstream policies violate World Trade Organization (WTO) provisions, namely Article XI:1 of the General Agreement on Tariffs and Trade (GATT) 1994. In the panel report, the World Trade Organization Dispute Settlement Body (WTO DSB) decided that Indonesia had been proven to have violated these WTO provisions. This thesis examines whether the WTO's ruling on Indonesia's restrictions on raw materials is justified and explores Indonesia's arguments in Appellate Body with the European Union regarding restrictions on nickel ore exports and downstreaming. The research methodology involves normative legal research, analyzing primary legal sources like legislation and secondary sources such as textbooks and case studies. The study delves into Indonesia's challenges in defending its policies at the WTO's Appellate Body. The primary research object is Indonesia's Measures relating to Raw Materials, particularly nickel ore, and relevant agreements like GATT 1994. Legal materials include Indonesian regulations on exports and GATT 1994, while secondary sources encompass statutory regulations, scientific journals, and related literature. The data collection method relies on library research. Using a qualitative approach, the thesis seeks a deep understanding of the core issues. Analytical methods include statutory interpretation, case studies, and grounded theory. The research finds Indonesia's measures non-compliant with GATT 1994 but suggests leveraging Article XXI, the Security Exception, as a strategic defense in the Appellate Body.